2015 International Joint Conference on Neural Networks (IJCNN) 2015
DOI: 10.1109/ijcnn.2015.7280539
|View full text |Cite
|
Sign up to set email alerts
|

Face expression recognition with a 2-channel Convolutional Neural Network

Abstract: A new architecture based on the Multi-channel Convolutional Neural Network (MCCNN) is proposed for rec ognizing facial expressions. Two hard-coded feature extractors are replaced by a single channel which is partially trained in an unsupervised fashion as a Convolutional Autoencoder (CAE). One additional channel that contains a standard CNN is left unchanged. Information from both channels converges in a fully connected layer and is then used for classification. We perform two distinct experiments on the JAFFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…Besides, different architectures of networks can be used to enhance the diversity. For example, a CNN trained in a supervised way and a convolutional autoencoder (CAE) trained in an unsupervised way were combined for network ensemble [142].…”
Section: Network Ensemblementioning
confidence: 99%
“…Besides, different architectures of networks can be used to enhance the diversity. For example, a CNN trained in a supervised way and a convolutional autoencoder (CAE) trained in an unsupervised way were combined for network ensemble [142].…”
Section: Network Ensemblementioning
confidence: 99%
“…Illumination invariance in the input images were overcome with LBP feature vectors along with the proposed SAX method. 2010Gaussian Process 93.43 Shih and Chuang (2008) DWT + 2D-LDA + SVM 95.71 Hamester et al (2015) Convolutional Neural Network 95.80 Poursaberi et al (2012) Gauss Laguerre wavelet+ KNN 96.71 Hegde et al (2016) Gabor and geometry based features 97.14 Proposed work LBP+SAX with Ensemble bag Classifier 98.7 (for 7 expressions JAFFE)…”
Section: Key Findingsmentioning
confidence: 99%
“…Hamester et al [2] proposed multi-channel convolutional neural networks (a standard CNN and a channel using pretrained parameters, which were obtained by a convolutional auto-encoder (CAE)) for facial expression recognition. Teixeira et al [3] have confirmed that convolutional neural networks significantly outperform conventional architectures such as LBP + SVM and SIFT + SVM.…”
Section: A Facial Expression Recognition Using Deep Learningmentioning
confidence: 99%